Correction: McBurnie et al. Training Management of the Elite Adolescent Soccer Player throughout Maturation. Sports 2021, 9, 170 - Alistair J. McBurnie; Thomas Dos'Santos; David Johnson; Edward Leng (MDPI AG, 2022)
The authors wish to make the following corrections to this paper [...]